Analysis of emerging technologies in the hydropower sector. (October 2019) - Kougias, Ioannis; Aggidis, George; Avellan, François; Deniz, Sabri; Lundin, Urban; Moro, Alberto; Muntean, Sebastian; Novara, Daniele; Pérez-Díaz, Juan Ignacio; Quaranta, Emanuele; Schild, Philippe; Theodossiou, Nicolaos
Abstract: The paper reviews recent research and development activities in the field of hydropower technology. It covers emerging and advanced technologies to mitigate flow instabilities (active and passive approach) as well as emerging magneto-rheological control techniques. Recent research findings on flow instabilities are also presented, especially concerning fluid-structure interaction and transient operating conditions. As a great number of the existing large-scale hydroelectric facilities were constructed decades ago using technologies that are now considered obsolete, technologies to achieve the digitalisation of hydropower are also analysed. Advances in the electro-mechanical components and generator design are presented; their potential role to adapt hydropower to the current operating conditions is also highlighted. The text explores current efforts to advance hydropower operation, mainly in terms of European projects. It provides a detailed overview of the recent efforts to increase the operational range of hydraulic turbines in order to reach exceptional levels of flexibility, a topic of several recent research projects. Variable speed hydropower generation and its application in pumped storage power plants are presented in detail. Moreover, revolutionary concepts for hydroelectric energy storage are also presented with the analysis focusing on underwater hydro storage and hydropower's hybridisation with fast energy storage systems. Efforts to minimise hydropower's environmental footprint are also presented via the utilisation of small-scale and fish-friendly installations. Highlights: Recent research and development activities in the field of hydropower technology are reviewed. Novel concepts of hydropower energy storage are presented. The perspective of the digitalisation of existing and new hydropower stations is analysed. Fish-friendly, environmental-friendly and small-scale hydropower solutions are outlined.